(untitled) (Research, Society and Development, 2021)
Objective: To analyze the scientific evidence available in the literature on the use of the Automatic External Defibrillator (AED) by lay people in pre-hospital care. Methodology: this is an integrative literature review. The search carried out identified 207 articles, 162 at PUBMED, 28 at LILACS and 17 at BDENF. The selection of articles for the preparation of the study began by excluding 27 duplicate articles in the databases; analysis of the titles, abstracts and descriptors of 180 articles was carried out. Thus, 29 articles were initially selected for full reading based on the inclusion criteria, considering the time frame from 2015 to 2020, where 17 articles were excluded, from which 12 full texts were listed for reading and synthesis. Results: It was evidenced that cases of cardiac arrests outside the hospital occur frequently in the world, leading to the frequent death of patients, it was also shown that early defibrillation can save such lives. The researches refer to a series of gaps in relation to the knowledge of technical measures and procedures of Basic Life Support (BLS) by lay people, as well as the use of AED in victims of cardiac arrests outside the hospital environment. Conclusion: The research synthesizes the scientific evidence available in the literature on DEA use by lay people in Prehospital care; the data point to a scenario that the identification of cardiorespiratory arrest outside the hospital environment and the early onset of maneuvers contained in BLS practices in victims of CPA is essential to increase survival.